Halal Tourism and Foreign Exchange Reserves in Indonesia: Error Correction Model - Suriani Suriani; Rahmatun Layali (Faculty of Economic and Business, 2022)
This study aims to look at how the number of tourists and the exchange rate affects Indonesia's foreign exchange reserves before and after the implementation of halal tourism from 2010 to 2019 (monthly). The Paired t-Test model was used to look at the differences in Indonesia before and after halal tourism. By examining the short and long-term effects of tourist numbers and currency rates on foreign exchange reserves using the Error Correction Model. Halal tourism, according to the research, helps Indonesia's foreign exchange reserves. The exchange rate has a negative impact on foreign exchange reserves in this situation. Meanwhile, the number of international visitors has a favourable impact on both short- and long-term foreign exchange reserves. It demonstrates that the tourism sector, particularly halal tourism, can be one of the supporting sectors in increasing the country's foreign exchange, encouraging the government to implement policies to support its tourism industry. How to Cite:Rahmatun, L., & Suriani. (2022). Halal Tourism and Foreign Exchange Reserves in Indonesia: Erroc Correction Model. Etikonomi, 21(1), 177-192. https://doi.org/10.15408/etk.v21i1.19616.